Upadacitinib versus placebo or adalimumab with background methotrexate in patients with rheumatoid arthritis and an inadequate response to methotrexate: a subgroup analysis of a phase III randomized controlled trial in Central and Eastern European patients - Karel Pavelka; Zoltán Szekanecz; Nemanja Damjanov; Branimir Anić; Matija Tomšič; Vadim Mazurov; Marija Maksimovic; Orsolya Nagy; Jerzy Świerkot; Tzvetanka Petranova; Tiina Veldi; Asta Baranauskaitė; et al. (BioExcel Publishing Ltd, 2020)
Background: In the randomized, phase III, global SELECTCOMPARE study, upadacitinib 15 mg demonstrated efficacy at week 12 versus placebo and adalimumab with methotrexate (MTX) in patients with rheumatoid arthritis and inadequate response to MTX, which was maintained over 48 weeks. This post hoc analysis of SELECT-COMPARE reports the efficacy and safety of upadacitinib in Central and Eastern European (CEE) patients. Methods: Patients were randomized 2:2:1 to upadacitinib 15 mg once daily, placebo, or adalimumab 40 mg every other week, and continued MTX. Efficacy and safety were assessed through 48 weeks. Primary endpoints were the achievement of ≥20% improvement in American College of Rheumatology response criteria and Disease Activity Score in 28 joints with C-reactive protein <2.6 responses at week 12 for upadacitinib versus placebo. No statistical comparisons were conducted. Results: A total of 596 patients from 12 CEE countries were randomized. At week 12, a numerically greater proportion of patients receiving upadacitinib versus placebo or adalimumab achieved ≥20% improvement in American College of Rheumatology response criteria (72% versus 33% and 59%), Disease Activity Score in 28 joints with C-reactive protein <2.6 (26% versus 4% and 11%), low disease activity and remission, and improved physical function, with results maintained over 48 weeks. Upadacitinib treatment numerically inhibited structural progression versus placebo at week 26. Serious infection and herpes zoster rates were numerically higher with upadacitinib versus adalimumab (2.7 versus 1.7 and 2.3 versus 1.1 events/100 patient-years, respectively) over 48 weeks. Conclusion: Consistent with the global population of patients with rheumatoid arthritis and an inadequate response to MTX, in CEE patients, upadacitinib 15 mg demonstrated clinical and functional improvements versus placebo and adalimumab, radiographic improvements versus placebo, and reasonable safety, over 48 weeks.